2016
DOI: 10.1093/mnras/stw3243
|View full text |Cite
|
Sign up to set email alerts
|

Faint progenitors of luminousz ∼ 6 quasars: Why do not we see them?

Abstract: Observational searches for faint active nuclei at z > 6 have been extremely elusive, with a few candidates whose high-z nature is still to be confirmed. Interpreting this lack of detections is crucial to improve our understanding of high-z supermassive black holes (SMBHs) formation and growth. In this work, we present a model for the emission of accreting BHs in the X-ray band, taking into account super-Eddington accretion, which can be very common in gas-rich systems at high-z. We compute the spectral energy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 110 publications
(147 reference statements)
2
41
0
Order By: Relevance
“…The short phases of super-Eddington growth, followed by longer periods of quiescence, expected to occur in IMBHs (e.g., Volonteri & Rees 2005;Madau et al 2014;Pezzulli et al 2016) could also decrease the probability of detecting accreting BHs (Pezzulli et al 2017). Modeling the X-ray emission of accreting BHs at z ∼6 and taking into account super-Eddington accretion, Pezzulli et al (2017) found that faint AGN progenitors at z ∼6 should be luminous enough to be detected in current X-ray surveys even when accounting for maximum obscuration.…”
Section: Seed Bhs At High Redshiftsmentioning
confidence: 99%
“…The short phases of super-Eddington growth, followed by longer periods of quiescence, expected to occur in IMBHs (e.g., Volonteri & Rees 2005;Madau et al 2014;Pezzulli et al 2016) could also decrease the probability of detecting accreting BHs (Pezzulli et al 2017). Modeling the X-ray emission of accreting BHs at z ∼6 and taking into account super-Eddington accretion, Pezzulli et al (2017) found that faint AGN progenitors at z ∼6 should be luminous enough to be detected in current X-ray surveys even when accounting for maximum obscuration.…”
Section: Seed Bhs At High Redshiftsmentioning
confidence: 99%
“…To assess the possibility of detecting BH activity in the nuclei of high-z HyLIRGs, we compared the predicted X-ray luminosity in the (observed-frame) soft ([0.5 -2] keV) and hard ([2 -10] keV) X-ray bands with the flux limits of recent surveys. Following Pezzulli et al (2017), we modeled the X-ray luminosity of accreting BHs considering the primary emission from the hot corona and the reflection component due to the surrounding neutral medium. The first one is parametrized as a power law, Lν ∝ ν −Γ+1 e hν/Ec , with an exponential cutoff energy of Ec = 300 keV (Sazonov et al 2004;Yue et al 2013) and photon spectral index Γ = 0.32 log λ Edd + 2.27, that we assume to depend on the Eddington ratio λ Edd = L bol /L Edd (Brightman et al 2013).…”
Section: The X-ray Observability Of Bh Activity In High-z Hylirgsmentioning
confidence: 99%
“…5.c, the resulting net attenuation of fluxes by obscuration in the observed-frame soft X-ray band is about a factor of 2, while fluxes in the observed-frame hard X-ray band are almost unaffected by attenuation. This can be explained in terms of the photoelectric cross section decreasing for increasing energy (see a thorough discussion in Pezzulli et al 2017). Finally, we compared the predicted, obscuration-attenuated F BH X with the flux limits obtained by Chandra observations of the recent 7 Ms Chandra Deep Field South Survey (7 Ms CDF-S; Luo et al 2017), i.e., FCDF−S = 6.4 × 10 −18 erg s −1 cm −2 in the soft band and FCDF−S = 2.7 × 10 −17 erg s −1 cm −2 in the hard band.…”
Section: The X-ray Observability Of Bh Activity In High-z Hylirgsmentioning
confidence: 99%
“…Our flux calculations and subsequent estimates on the number of observable quasars should therefore be taken as upper limits. However, the results of Pezzulli et al (2017) indicate that even if absorption is important, the overall effect out to z∼10 is not expected to be severe enough to impact our results.…”
Section: Soft X-ray Emissionmentioning
confidence: 76%
“…Since the greatest sensitivity to the emission produced in our model occurs in soft X-rays (see, e.g., Pezzulli et al 2017), we consider only the soft X-ray band between ò l =0.5 keV and ò u =2 keV. For a BH at redshift z, the luminosity emitted in this band is given by the expression…”
Section: Soft X-ray Emissionmentioning
confidence: 99%